2020
DOI: 10.1021/acsapm.0c00929
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Generating Polymer Particles: Reducing the Decomposition Temperature of Poly(tert-Butyl Methacrylate) Side Chains Using an Encapsulated Acid Catalyst Approach

Abstract: We report an approach to gas-generating polymer particles based on the acid-catalyzed thermal decomposition of poly(tert-butyl methacrylate) [p(t-BMA)] side chains to isobutene gas. The decomposition temperature of t-BMA latex is near 191 °C and therefore impractical for many applications. The incorporation of select acid functionalized comonomers yields a decrease to ∼160 °C, as determined by thermal gravimetric analysis. This temperature can be further reduced to ∼120 °C, however, via encapsulation of a ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[89] Amino functionalized silica spheres employ as a template to synthesize Pt spheres. [90] These spheres contain nano-sponge like shell and hollow interior generated by mixing precursor solution of platinum with silica spheres. [91] 0.1 M ascorbic acid added for the complete synthesis of platinum nanoparticles.…”
Section: Polystyrene Templatesmentioning
confidence: 99%
“…[89] Amino functionalized silica spheres employ as a template to synthesize Pt spheres. [90] These spheres contain nano-sponge like shell and hollow interior generated by mixing precursor solution of platinum with silica spheres. [91] 0.1 M ascorbic acid added for the complete synthesis of platinum nanoparticles.…”
Section: Polystyrene Templatesmentioning
confidence: 99%
“…Poly( tert ‐butyl methacrylate) (PTBMA) has applications in broad areas including but not limited to vapor sensing, [ 14 ] thermal lithography, [ 15 ] additives, [ 16 ] and drug delivery. [ 17 ] RDRP of TBMA was achieved via ATRP, [ 18 ] RAFT polymerization, [ 19 ] emulsion polymerization, [ 20 ] nitroxide‐mediated polymerization (NMP), [ 21 ] and photoinduced free radical polymerization. [ 22 ] It is observed that these polymerization processes usually led to polymers with undesired odor, color, and toxicity because of the presence of sulfur chain ends (for RAFT), [ 23 ] catalyst leaching (for ATRP), [ 24 ] inefficient removal of Cu(I)/Cu(II) precursors (for SET‐LRP) [ 25 ] preventing the development of more environment‐friendly polymerization processes.…”
Section: Introductionmentioning
confidence: 99%